Global research characteristics and trends of artificial intelligence for scoliosis: a bibliometric analysis (2014-2023) - Yang, Jie-ke; Han, Li-li; Wang, Jia-wei; Zhou, Ning-jing; Zhou, Ke-wang (Journal of the Pakistan Medical Association, 2025)
The integration of Artificial Intelligence into medical fields is transforming clinical practices, but its role in scoliosis — a condition requiring complex diagnostic and management strategies — remains underexplored. The current narrative review was planned to analyse global research trends in Artificial Intelligence applications to scoliosis from 2014 to 2023 using a bibliometric approach. Data from 627 publications, authored by 562 researchers across 57 countries, was extracted from the Web of Science Core Collection, and analysed using CiteSpace 6.3.R1. Results revealed a surge in publications since 2017, peaking in 2021, with a thematic shift from surgical interventions to perioperative management. The United States leads in both contributions and advancements, with Spine as the top journal. Future research should focus on optimising Artificial Intelligence algorithms and integrating them into clinical decision-making to enhance scoliosis management and patient outcomes. Key Words: Scoliosis, Artificial intelligence.